The gut-brain axis in the context of colorectal cancer - Hao Wu; Kexin He; Hao Wang; Weihan Li; Ruixue Huo; Shu-Heng Jiang; Junli Xue (Pharmacological Research)
The gut-brain axis (GBA) plays a pivotal role in the pathophysiology of colorectal cancer (CRC), influencing tumor progression, immune responses, and therapeutic outcomes. Bidirectional communication between the gut and the brain, mediated through microbial metabolites, neurotransmitters, and neural signaling pathways, shapes the tumor microenvironment and systemic inflammation. CRC cells not only modify the gut microbiota but also release neuroactive molecules that influence neural circuits, further impacting tumor growth. The autonomic nervous system regulates gut motility, immune responses, and inflammation, contributing to CRC progression. The gut microbiome’s production of bioactive molecules, such as short-chain fatty acids and neurotransmitters, further modulates brain activity, promoting tumor metastasis and immune evasion. This review summarizes the complex interactions within the GBA and their implications for CRC, with a focus on immune modulation, microbial dysbiosis, and neuroimmune interactions. We highlight the therapeutic potential of targeting the GBA, including microbiome modulation, neurotransmitter-specific therapies, and psychological interventions, which could complement existing CRC treatments. Future research is essential to further elucidate the precise molecular mediators of the GBA and their impact on CRC biology, laying the groundwork for novel, targeted therapeutic strategies that could improve patient outcomes.